Management of “Awal Minggu Podcast” production during pandemic - Muhammad Afif Ardhi; Filosa Gita Sukmono; Adinda Putri Surya Kencana (Manajemen Komunikasi, 2023)
This study exposes the production management of the Awal Minggu Podcast during the pandemic. Podcasts were indeed one of the new broadcasting media which formed a new industry, especially in Indonesia. At the beginning of its establishment in 2015, Awal Minggu Podcast became one of the pioneers of podcasts in Indonesia with the main theme of monologue. This study aimed to examine the Awal Minggu Podcast production management during the pandemic. This research used descriptive qualitative methods using a scientific background and involving phenomena that occurred at that time and carried out using existing methods. The data were collected through in-depth interviews, documentation, and related literature. Interviews were conducted online using Zoom and Email with two speakers, namely Adriano Qalbi and Billa Ayu Kinanti, as podcasters and line producers of the Awal Minggu Podcast. The findings found that the Awal Minggu Podcast carried out some steps in its production: pre-production, production, and post-production. The research shows that the Awal Minggu Podcast can effectively and efficiently utilize the management function in producing audio-visual podcast recordings. The basic management functions such as planning, organizing, directing, and supervising are implemented by the Awal Minggu Podcast as support for successful production to get the expected results so that the Awal Minggu Podcast remains productive during the pandemic.